Potentials of Non-Invasive 18F-FDG PET/CT in Immunotherapy Prediction for Non–Small Cell Lung Cancer - Liao, Xuhe; Liu, Meng; Wang, Rongfu; Zhang, Jianhua (Frontiers in Genetics, 2022)
The immune checkpoint inhibitors (ICIs) by targeting cytotoxic-T-lymphocyte-associated protein 4, programmed cell death 1 or PD1-ligand 1 has dramatically changed the natural history of several cancer including non-small cell lung cancer (NSCLC). There are unusual response manifestations (such as pseudo-progression, hyper-progression and immune-related adverse events) observed in patients with ICIs since the unique mechanisms of these agents. These specific situations render response and prognostic assessment to ICIs challenging. This review will demonstrate how 18F-FDG PET/CT can help to identify these unusual response patterns in a non-invasive effective way. Then a series of semi-quantitative parameters derived from 18F-FDG PET/CT will be introduced. The latest studies on baseline semi-quantitative method to predict the response and prognosis for NSCLC patients with ICIs are summarized and discussed. And current situation on functional criteria based on 18F-FDG PET/CT for immunotherapeutic response assessment are presented and analyzed. From these parts, 18F-FDG PET/CT has been adopted as a non-invasive effective approach to predict the efficacy to immunotherapy and prognosis, screen the population who can benefit from the ICIs, identify various responses, and dynamically evaluate the sensitive and resistant status during immunotherapy. Although 18F-FDG PET/CT parameters have been reported to be associated with efficacy and prognosis in NSCLC patients treated with ICIs, especially volumetric indexes and response assessment criteria based on PET/CT proposed resolutions to overcome limitations of morphologic criteria in response assessment, the limitations, especially lack of specificity, have restrict the spread in the field of immunotherapy. The second part will display present status and a prospective of novel PET probes targeting to key molecules relevant to immunotherapy in prediction and response assessment.